Costs, Preferences, and Institutions: An Empirical Analysis of the Determinants of Government Decentralization - Dan Stegarescu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper examines the factors determining vertical government structures. An empirical analysis for a panel of OECD countries indicates that apart from preferences, economies of scale, and other factors, institutions explain cross-national differences in the degree of fiscal decentralization. Accounting for taxing powers of subnational governments, the evidence strongly supports the collusion hypothesis according to which delegation of decision-making concerning the assignment of powers and national legislation to subnational representatives leads to increased tax centralization, as compared to direct participation of the citizens of the subnational entities. On the other hand, direct democracy at the national level is associated with higher centralization.
Keywords: H72; H71; H77; 330; Determinants of Decentralization; Decision-making Institutions; Decentralization Theorem; Collusion Hypothesis; Dezentralisierung; Finanzföderalismus; Politische Entscheidung; Politisches System; Schätzung; OECD-Staaten